Teacher's Strategy in Instilling Disciplined Characters in Class IV Students at SDN 2 Kalijaga - Zaepi Aspiani; Darmiany Darmiany; Husniati Husniati (IKIP Mataram, 2022)
The character of discipline can be interpreted as an attitude of obedience, submission and obedience to various applicable provisions and regulations. With a disciplined character, students are expected to become more responsible individuals, accustomed to something that makes them develop, do things on time and obey the values and rules that apply wherever they are. To achieve this goal, the teacher in this case really needs a strategy in its efforts. This study aims to describe the teacher's strategy in instilling the disciplined character of fourth grade students at SDN 2 Kalijaga. This research is a descriptive qualitative research with the type of phenomenology. The subjects in this study were the principal of SDN 2 Kalijaga, fourth grade teachers, and fourth grade students with the object of research being the teacher's strategy. Data were collected by means of interviews, observation and documentation. Data analysis was carried out using the Miles and Huberman model technique, namely data reduction, data presentation and conclusion drawing. The validity of the data was tested by using triangulation of sources and triangulation of data collection techniques. As for in this study, there are several strategies applied by teachers, namely integration in learning, establishing school rules, holding scout extracurriculars, exemplary values from teachers, giving sanctions/punishments, making policies in the form of new programs such as a joint prayer program in the field before start learning and picket schedule for the cleanliness of the school environment.